Error Analysis of Errors in Arabic Phonetics at the University - Dewi Ayu Amalya; Khizanatul Hikmah (Indonesian Journal of Islamic Studies, 2023)
Ma'had prepares the mustawa robi' class to produce female students who like to speak Arabic and can speak Arabic correctly, so that they can graduate with mumtaz predicate and can practice the knowledge they got when studying at Mahad Umar bin Khattab. The most important thing in learning Arabic is in learning listening skills where students listen to the teacher in explaining a title using Arabic sounds, and female students will present the title that has been explained in front of their friends using good and correct Arabic sounds. So the objectives of this study are: 1) to find out the Arabic sound errors. 2) to find a solution to the problems contained in the Arabic sound error. This research uses a qualitative approach with a descriptive type of research. The data collection techniques in this research by observations, interviews and documentation. The data analysis technique used in this research is Miles and huberman data analysis technique, as: The data reduction, data presentation and conclusion drawing. The results showed that: 1) mispronunciations of words, both in terms of phonetics, grammar and morphology. 2) Problem solving in Arabic voice is through continuous practice of speaking in Arabic voice, preparation before explaining the subject, and motive to be more confident.